Youth empowerment through humanising entrepreneurship education programme in Afghanistan for jobs creation - Wasiq, Shafiullah; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2019)
Entrepreneurship is considered a key factor for economic growth and the development of a country. This is because it has the potential of creating millions of job opportunities. Entrepreneurship provides opportunities in offering a variety of consumer goods and services, and generally help in reducing poverty in the society. Because of this positive effect of entrepreneurship, in the recent two decades entrepreneurship education has grown rapidly all over the world including in Afghanistan. In the middle of this development remains the issues and challenges confronting the Afghan youth, ranging from severe poverty, youth unemployment and dependence of youth solely on government jobs. This paper therefore argues the importance of entrepreneurship education in Afghanistan for empowering youths to be self-employment, to create decent job and to contribute to the well-beings of society.This paper adapted the design thinking and system thinking approach to solve the youth problems in Afghanistan through understanding their needs by building and developing business models using tools such as Business model canvas (BMC) and Value proposition design canvas (VPC). The approach includes conducting literature review and interviews for understanding the key problems; formulating and ideating initial business model options in solving the problems; and validation of business model by interviewing the customer segments. Finally, the main contribution of this paper is to provide a conceptual business models, validated BMC and VPC, and implement humanising Entrepreneurship education programmes in Afghanistan in order to nurture youths with the knowledge, skills and virtues. This paper also contributed on how to educate youth in Afghanistan to become responsible entrepreneurs who can startup their own businesses and hence contributing to the societal well-being.